Bending analysis of simply-supported sandwich beam using Chebyshev quadrature element method. Issue 1 (February 2021) - Ge, Meng; Zhao, Yang; Huang, Yixin; Ma, Wenlai
Abstract: Based on the higher-order sandwich beam theory, the Chebyshev quadrature sandwich beam element is established for the bending analysis of the simply-supported sandwich beam. Gauss Lobatto sampling is adopted as element nodes. The discrete governing equation of the sandwich beam is obtained by the principle of minimum potential energy. A series of numerical examples are carried out on simply-supported sandwich beams under sinusoidal loading. The results are compared with the finite element method, showing that the proposed method can yield very accurate displacements and stresses. This method is suitable for the static analysis of simply-supported sandwich beams with different materials and different geometric parameters.